Exome sequencing identifies titin mutations causing hereditary myopathy with early respiratory failure (HMERF) in families of diverse ethnic origins - Toro, Camilo (BioMed Central, 2013)
BACKGROUND: Hereditary myopathy with early respiratory failure (HMERF) was described in several North European families and recently linked to a titin gene (TTN) mutation. We independently studied HMERF-like diseases with the purpose to identify the cause, refine diagnostic criteria, and estimate the frequency of this disease among myopathy patients of various ethnic origins. METHODS: Whole exome sequencing analysis was carried out in a large U.S. family that included seven members suffering from skeletal muscle weakness and respiratory failure. Subsequent mutation screening was performed in further 45 unrelated probands with similar phenotypes. Studies included muscle strength evaluation, nerve conduction studies and concentric needle EMG, respiratory function test, cardiologic examination, and muscle biopsy. RESULTS: A novel TTN p.Gly30150Asp mutation was identified in the highly conserved A-band of titin that co-segregated with the disease in the U.S. family. Screening of 45 probands initially diagnosed as myofibrillar myopathy (MFM) but excluded based on molecular screening for the known MFM genes led to the identification of a previously reported TTN p.Cys30071Arg mutation in one patient. This same mutation was also identified in a patient with suspected HMERF. The p.Gly30150Asp and p.Cys30071Arg mutations are localized to a side chain of fibronectin type III element A150 of the 10th C-zone super-repeat of titin. CONCLUSIONS: Missense mutations in TTN are the cause of HMERF in families of diverse origins. A comparison of phenotypic features of HMERF caused by the three known TTN mutations in various populations allowed to emphasize distinct clinical/pathological features that can serve as the basis for diagnosis. The newly identified p.Gly30150Asp and the p.Cys30071Arg mutation are localized to a side chain of fibronectin type III element A150 of the 10th C-zone super-repeat of titin.